Analysis of famer income levels at traditional markets in Lohia Sapalewa village, Taniwel district wets Seram regency - Rio D Tibalilatu; Weldemina B. Parera; D. Leatemia (International Journal of Economics, Business and Innovation Research, 2023)
The study was carried out in Lohia Sapalewa village, Taniwel District, West Seram Regncy, Maluku Province from June to July 2021. This research aims to analyze the income level of farmers in the village of Lohia Sapalewa whit a market in the mountainous region of Taniwel. The research was carried out using a random sampling method as many as 27 people (20%) from 135 farmers. Data retrieval was taken using the primary data method from careful comprehensive field observations as well as secondary data by searching documents on various references. The results of the study found that the presence of the market had a positive impact on the farming community in Lohia Sapalewa Village, this was proven by the increasing income of farmers in Lohia Sapalewa village and the presence of the market made the community feel able to fulfill their dailyneeds, both household needs, children's education. As well as accessing health services